Respuesta :

Answer:

-(1 - 2a)^2

Step-by-step explanation:

-1 + 4a - 4a^2

= -[1^2 - 2*1*(2a) + (2a)^2]

= -(1 - 2a)^2

Answer:

Step-by-step explanation:

Begin by taking out the minus

-(4a^2 - 4a + 1)     The answer is the square root of the 1st and 3rd terms.

√4a^2 = 2a

√1 = 1                    Since middle term is minus, one of 2a or 1 must also be minus

Usually the one is made minus.

That leaves you with a perfect square

- (2a - 1)^2   There are more ways than 1 to write this, but I think this is the clearest answer

ACCESS MORE